Eksplorasi Korelasi Gender Sebagai Mediator dalam Keterlibatan Anak di Taman Kanak-Kanak - Sakri Alfaregi, Ilham; Hartati, Sofia; Akbar, Zarina (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to explore the correlation between gender as a mediator in children's engagement in kindergarten, using a quantitative approach with a correlational design. The study involved 70 children aged 5-6 years at Fadillah Amal 3 Kindergarten, Padang City, West Sumatra. The research instrument consisted of 42 questions, divided into 22 items related to engagement and 20 items related to gender, using a Likert scale with scores ranging from 1 to 5. Data collection was conducted through questionnaires filled out by classroom teachers. The results indicate a significant correlation between gender and children's engagement. The Pearson correlation test showed a coefficient value of 0.877, indicating a strong positive relationship between the gender variable and engagement. Further Paired Sample Test analysis revealed significant differences in children's engagement based on gender, with girls showing higher levels of engagement compared to boys. The determination coefficient test demonstrated that gender strongly contributes to children's engagement in kindergarten, with a coefficient value of 0.77 for the overall relationship, 0.788 for boys, and 0.53 for girls. These findings highlight the importance of considering gender differences when designing inclusive and effective learning strategies in early childhood education environments. This research provides valuable insights for educators and parents in enhancing children's engagement in kindergarten through gender-sensitive approaches.